Te Vacancy‐Driven Anomalous Transport in ZrTe5 and HfTe5 - Elizabeth A. Peterson; Christopher Lane; Jian‐Xin Zhu (Advanced Physics Research, 2025)
Abstract The strongly sample‐dependent anomalous transport properties observed in the layered Dirac materials ZrTe5 and HfTe5 are known to strongly correlate with the presence of Te vacancies. One phenomenon, a negative longitudinal magnetoresistance (NLMR), is widely speculated to be a signature of broken chiral symmetry. However, the role of electronic structure in the sample dependence of the transport properties of these materials is poorly understood. This prompts the question as to whether the NLMR is a genuine signature of the chiral anomaly in ZrTe5 and HfTe5. In this work, the effect of Te vacancies on the electronic structure of ZrTe5 and HfTe5 is investigated via first‐principles calculations. Te vacancies serve two purposes: modification of the cell volume via effective compressive strain and production of local changes to the electronic structure. The reorganization of the electronic structure near the Fermi energy indicates that Te vacancies can rationalize conflicting reports in spectroscopic and transport measurements that have remained elusive in prior first‐principles studies. These results show that Te vacancies contribute, in part, to the anomalous transport properties of ZrTe5 and HfTe5 but, critically, do not eliminate the possibility of a genuine manifestation of the chiral anomaly in these materials.